Performance of two rapid point of care SARS-COV-2 antibody assays against laboratory-based automated chemiluminescent immunoassays for SARS-COV-2 IG-G, IG-M and total antibodies - Lau, C. S. (Elsevier B.V., 2022)
10.1016/j.plabm.2021.e00201